E a máquina livro virou na máquina jogo: sistematização de uma experiência pedagógica baseada na obra literária "Macunaíma", de Mário de Andrade - Albuquerque, Thiago Camargo de (2018)
The Multimedia Education Group of the Federal University of Rio de Janeiro (GEM / UFRJ) promoted two editions of a pilot program that had as a proposal the translation of Macunaíma, by Mario de Andrade, into analog games. These courses were held at the Federal Institute of Technological Education of Rio de Janeiro and at the GEM’s laboratory. Based on this experience, this dissertation sought to offer data that allowed the analysis of the limits and possibilities of developing workshops to translate languages between literature and analog games in the scope of the Projeto Travessias: Palavra-Imagem, which has been spearheaded by GEM for ten years. It was, therefore, a systematization of a set of experiences (HOLLIDAY, 2006) concerning the program, from its formulation to the final evaluation by its participants. The formulation of the program and, consequently, this dissertation allowed the connection of apparently distant areas of knowledge such as Education, Literature, Game Studies and Translation. Based on work as an educational principle (SAVIANI, 1989), the program organized the participants around an inter-semiotic translation activity (PLAZA, 2003), which consisted of a group interpretation of the Mário de Andrades’s rhapsody (ANDRADE, 1984) through the contribution of critical materials (SOUZA, 1979) (PROENÇA, 1987) in order to develop board games similar to the material studied. In this way, the essential experience provided by the game (SCHELL, 2008) and its emergent narratives (SALEN and ZIMMERMAN, 2012) sought to refer to the original work, making use mainly of its mechanics. The systematization presented data and bearings for the improvement of similar activities in future Projeto Travessias’ actions, as well as possibilities of appropriation of these materials by educational professionals interested in promoting activities based on principles of interdisciplinarity, socio-interactionism and polytechnics.